Risk, reassurance and routine: a qualitative study of narrative understandings of the potential for HIV self-testing among men who have sex with men in England - T. Charles Witzel; Peter Weatherburn; Alison J. Rodger; Adam H. Bourne; Fiona M. Burns (BMC, 2017)
Abstract Background HIV testing has seen a rapid evolution over the last decade with multiple modalities now in use globally. In recent years HIV self-testing (HIVST) has been legalised in the UK paving the way for further expansion of testing. Interventions are delivered in particular social contexts which shape uptake. It is therefore important to understand how novel interventions are likely to be received by their intended users. This study aims to understand how HIVST compliments existing testing strategies considered or adopted by men who have sex with men (MSM). We do this by analysing normative discourses surrounding HIV testing and their perceptions of HIVST's potential future roles. Methods Six focus group discussions (FGDs) were conducted with 47 MSM in London, Manchester and Plymouth. One focus group included only MSM who reported higher risk behaviours and one with those who had never tested for HIV. Data were analysed through a thematic framework analysis. Results Three main narratives for testing for HIV were identified: (i) testing in response to a specific risk event; (ii) as reassurance when there was a small amount of doubt or anxiety related to HIV; and (iii) in response to social norms perpetuated through peers, HIV community groups and the medical establishment to test regularly for HIV. HIVST had limited utility for men when testing in response to specific risk events except in the case of significant structural barriers to other testing opportunities. HIVST was considered to have utility when seeking reassurance, and was thought to be very useful when testing to satisfy the needs and expectations of others around regular testing. There was some ambivalence about the incursion of a clinical intervention into the home. Conclusions HIVST following risk events will likely be limited to those for whom existing service provision is insufficient to meet immediate needs based on structural or personal barriers to testing. Obligations of biological citizenship are central to MSM's understanding of the utility of HIVST. In the context of discourses of biocitizenship, men perceive HIVST to have dual roles: firstly as a tool to manage (mild) anxiety around one's HIV status based on an acknowledgment of HIV vulnerability arising from being homosexually active. Secondly, HIVST is useful in complying with social norms and meeting the perceived demands of biomedicine.